Study on the Efficiency of Metal Modified Bio–Nanocomposite Bead for Removal via Retention of Some Anthraquinone Dye - Mitali Sarkar; Dhiman Santra; Shanku Denrah; Swagatam Sarkar; Pankaj Sarkar (Challenges and Advances in Chemical Science Vol. 3, 2021)
In an aim to study the efficiency of metal modified bio–nanocomposite bead for removal via retention of anionic dye the batch adsorption tests were conducted with iron(III) loaded cellulose nanocomposite bead and alizarin red S, of different concentrations, from aqueous environment. The spectral and surface character of the bead was investigated. The process was optimized for variables (pH, contact time, initial dye concentration, adsorbent dose, temperature), employing response surface methodology following full factorial and central composite design. The maximum adsorption of 97% was observed at an optimum condition of pH 3.0, dose of 2.0 gdm-3 and shaking time of 45 mins corresponding to the dye concentration of 100 mgdm-3 at 303 K. The influence of the significant variables was correlated with the extent of dye adsorption in a second order polynomial equation. The mutual interactions of the significant variables were presented by 3D response surface and 2D contour plots in the design space. The adsorption was better described by Langmuir isotherm and pseudo second order kinetics. The process was spontaneous (-\(Δ\)G°, 48.19 kJmol-1), feasible (\(Δ\)S°, 0.284 Jmol-1K-1) and endothermic (\(Δ\)H°, 71.62 kJmol-1). The adsorbent can be regenerated with NaOH (10.0.10-2 M) and recycled for reuse, at least for five successive operations.